1999
DOI: 10.1093/ajcn/69.6.1189
|View full text |Cite
|
Sign up to set email alerts
|

Resting energy expenditure in reduced-obese subjects in the National Weight Control Registry

Abstract: Background: Weight loss in obese subjects is associated with a reduction in resting metabolic rate (RMR). Whether the reduction can be explained solely by a reduction in lean body mass remains controversial. Objective: Our objective was to determine whether the reduction in RMR after weight loss was proportional to the decrease in lean mass alone or was greater than could be explained by body composition. Design: We measured the RMR, fasting respiratory quotient (RQ), and body composition in 40 reduced-obese s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
2
5

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 23 publications
4
47
2
5
Order By: Relevance
“…Astrup et al (1999) showed that lower RMR values are usually found in (normal-weight) post-obese subjects compared to normalweight subjects and concludes that the obese state is at least partly the consequence of this lower metabolic rate. However, in a study of Wyatt et al (1999) no evidence was found that weight loss results in a lower than expected RMR, suggesting that many people will have a normal RMR after weight loss. It is well known that, although many obese individuals are able to lose weight, most cannot maintain the weight loss for longer periods.…”
Section: Resting Metabolic Rate In Italiansmentioning
confidence: 92%
“…Astrup et al (1999) showed that lower RMR values are usually found in (normal-weight) post-obese subjects compared to normalweight subjects and concludes that the obese state is at least partly the consequence of this lower metabolic rate. However, in a study of Wyatt et al (1999) no evidence was found that weight loss results in a lower than expected RMR, suggesting that many people will have a normal RMR after weight loss. It is well known that, although many obese individuals are able to lose weight, most cannot maintain the weight loss for longer periods.…”
Section: Resting Metabolic Rate In Italiansmentioning
confidence: 92%
“…7 Increased sedentary behaviour is an important factor in the development of human obesity. 10 Whilst low-resting energy expenditure may contribute to obesity, 11,12 recent research has indicated it has minimal impact on weight gain 13,14 and activity-related energy expenditure may be much more important. 15 It has been reported that low physical activity accounted for 77% of weight gain over a year in one prospective study 16 and inactivity is a major determinant of increased adiposity during overfeeding.…”
Section: Introductionmentioning
confidence: 99%
“…However, high levels of exercise are reported by many obese individuals who successfully maintain long-term weight loss (26). Their success may be partly due to the fact that exercise prevents the reduction in metabolic rate, which usually accompanies chronic weight loss (27,28). Even so, this highly motivated group represents only a small percentage of the overall population of postobese individuals who are able to successfully maintain long-term weight loss.…”
mentioning
confidence: 99%